Repetitive Anal Intercourse as a Potential Risk for Renal Failure - Hegazy, Dr. Abdelmonem (Academia Anatomica International, 2017)
Homosexual intercourse has been more frequently reported nowadays.[1,2] At the same time, there is an increasing population of patients with chronic renal insufficiency.[3] Many people have misconceptions that both urine and stool are waste products of the same quality. Therefore intromission of the penis into the rectum has no harm for both partners, as the organs carry similar products. This motivates some young male youths to elect the anal sex over penile-vaginal penetrative intercourse in order to preserve the virginity of their female partners, especially before marriage. In many cultures, the virginity of females should be safeguarded till marriage.[4] After marriage, some couples may shift to anal sex as practiced as a mean of contraception.[5] Also, others may practice it as a fantastic, foreplay and as mode of change in their sexual life. There may be psychological disorders in persons practicing unsafe anal sex.[6] The motives for such high risk sexual practices with men are mostly non sexual needs but may be due to other causes e.g. search of experiences or offset shortcomings and feelings of emotional loneliness.[7]